2015
DOI: 10.1094/pdis-07-14-0755-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Alternaria alternata Causing Leaf Spot on Bruguiera gymnorrhiza in China

Abstract: 2(Ch|). Pathotype 39(P,) was detected in small garden potato plots in the rainy mountainous area, a non-economically important potato-growing region where the old traditional cultivars of potato are cultivated without crop rotations. It seems, therefore, that where climatic conditions are suita ble for 5. endobioticum and the growing of slightly susceptible cultivars is possible, development of the new pathotype is favored.London planetrees (Platanus x acerifolia, syn. P. x hispanica), American sycamores (P. o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…According to several previous reports, all isolates of A. alternata isolated from several hosts produced dark olive green colonies on the PDA medium with dark brown conidia at 25 ± 2°C in a dark environment (Chen et al, 2018;Ghuffar et al, 2018;Alam et al, 2019), and the size of the conidia was 12-30-μm long and 7.5-12 μm wide (Gur et al, 2017;Chen et al, 2018;Moosa et al, 2019). Previous studies reported similar results that the length of conidia varied from 0 to 10 μm (Kumar et al, 2012;Lin et al, 2015). The causal organism of sweet cherry rot was preliminarily identified as A. alternata based on their morphological features (Simmons, 2007).…”
Section: Discussionmentioning
confidence: 70%
“…According to several previous reports, all isolates of A. alternata isolated from several hosts produced dark olive green colonies on the PDA medium with dark brown conidia at 25 ± 2°C in a dark environment (Chen et al, 2018;Ghuffar et al, 2018;Alam et al, 2019), and the size of the conidia was 12-30-μm long and 7.5-12 μm wide (Gur et al, 2017;Chen et al, 2018;Moosa et al, 2019). Previous studies reported similar results that the length of conidia varied from 0 to 10 μm (Kumar et al, 2012;Lin et al, 2015). The causal organism of sweet cherry rot was preliminarily identified as A. alternata based on their morphological features (Simmons, 2007).…”
Section: Discussionmentioning
confidence: 70%
“…(CCS) was a deciduous tree and shrub of the lacquer tree family that was mainly distributed in southern Europe, Iran, Pakistan, northern India, southwestern China, North China, and Zhejiang. It is typically used as a shelter forest for water and soil conservation and for landscaping [ 1 , 2 , 3 , 4 ]. In addition, CCS contains various chemical components, such as flavonoids and gallic acid, and is also a traditional medicinal plant in China.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the fungus was identified as A. alternata. A. alternata has a wide host range, including Ficus microcarpa, Bruguiera gymnorrhiza, and jujube (Bai et al 2015;Lin et al 2015;Yao et al 2015). This is the first report of A. alternata causing Alternaria brown spot on A. elata.…”
mentioning
confidence: 98%